Green criminology: shining a critical lens on environmental harm. Issue 1 (December 2017) - Nurse, Angus
Abstract Green criminology provides for inter-disciplinary and multi-disciplinary engagement with environmental crimes and wider environmental harms. Green criminology applies a broad ''green'' perspective to environmental harms, ecological justice, and the study of environmental laws and criminality, which includes crimes affecting the environment and non-human nature. Within the ecological justice and species justice perspectives of green criminology there is a contention that justice systems need to do more than just consider anthropocentric notions of criminal justice, they should also consider how justice systems can provide protection and redress for the environment and other species. Green criminological scholarship has, thus, paid direct attention to theoretical questions of whether and how justice systems deal with crimes against animals and the environment; it has begun to conceptualize policy perspectives that can provide contemporary ecological justice alongside mainstream criminal justice. Moving beyond mainstream criminology's focus on individual offenders, green criminology also explores state failure in environmental protection and corporate offending and environmentally harmful business practices. A central discussion within green criminology is that of whether environmentalharm rather than environmental crime should be its focus, and whether green ''crimes'' should be seen as the focus of mainstream criminal justice and dealt with by core criminal justice agencies such as the police, or whether they should be considered as being beyond the mainstream. This article provides an introductory overview that complements a multi- and inter-disciplinary article collection dedicated to green criminological thinking and research.